2021
DOI: 10.3390/antiox10050771
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Peroxisomal Activities and Nrf2 Signaling in Porcine Embryos

Abstract: Melatonin and phytanic acid (PA) are known to be involved in lipid metabolism and β-oxidation, in which peroxisomal activities also significantly participate. In addition, other studies have reported that the nuclear factor-erythroid-derived 2-like 2 (Nrf2 or NFE2L2) signaling pathway mediates lipid metabolism and its subsequent cascades. As these mechanisms are partially involved in porcine oocytes or embryonic development, we hypothesized that the factors governing these mechanisms could be interconnected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Both melatonin and phytanic acid have a role in this, as well as in the nuclear factor erythroid-derived 2-like 2 (referred to as Nrf2 or NFE2L2) signalling pathway. In a study by Kim et al, the interaction between peroxisomal activity and the Nrf2/NFE2L2 pathway, and the interaction with melatonin combined with phytanic acid in porcine embryos, was investigated [6]. The group used targeted siRNAs to silence the peroxisome biogenesis factor Pex19.…”
mentioning
confidence: 99%
“…Both melatonin and phytanic acid have a role in this, as well as in the nuclear factor erythroid-derived 2-like 2 (referred to as Nrf2 or NFE2L2) signalling pathway. In a study by Kim et al, the interaction between peroxisomal activity and the Nrf2/NFE2L2 pathway, and the interaction with melatonin combined with phytanic acid in porcine embryos, was investigated [6]. The group used targeted siRNAs to silence the peroxisome biogenesis factor Pex19.…”
mentioning
confidence: 99%
“…Therefore, gaining a deeper understanding of cellular responses to conditions that elevate oxidative stress is crucial for developing enhanced culture environments and generating healthy embryos and offspring. Previous studies have suggested that NRF2 serves as a critical mediator of the oxidative stress response in embryos 29 , 35 , 54 . However, the importance and role of NRF2 in porcine embryo development under a metabolically stressful environment has not been characterized through its specific inhibition with RNAi.…”
Section: Discussionmentioning
confidence: 98%
“…NRF2 has been shown to regulate oxidative stress in granulosa cells under stressful conditions 33 , and this function may involve interactions with miRNAs 34 . Furthermore, NRF2 induces peroxisomal activities in porcine oocytes and embryos 31 , 35 . The NRF2 signaling pathway involves numerous targets and regulates over 600 genes 36 , including more than 200 cytoprotective agents like heme-oxygenase 1 (HO1) and SIRT1.…”
Section: Introductionmentioning
confidence: 96%
“…This may be explained by the activation of exosomes during isolation. Xu et al suggested that the isolation process may cause changes in the size, shape, and protein contents of exosomes, affecting their functions and applications in clinical trials [ 38 ]; additionally, a study by Lobb et al showed that the functions of exosomes from human plasma and cell culture supernatant were regulated depending on the isolation methods [ 39 ]. This can be interpreted as isolated exosomes having different properties and better functions than intact exosomes.…”
Section: Discussionmentioning
confidence: 99%